A Substrate-Mimicking Basement Membrane Drives the Organization of Human Mesenchymal Stromal Cells and Endothelial Cells Into Perivascular Niche-Like Structures - Perugini, Valeria; Santin, Matteo (Frontiers in Cell and Developmental Biology, 2021)
Extracellular matrix-derived products (e.g., Matrigel) are widely used for in vitro cell cultures both as two-dimensional (2D) substrates and as three-dimensional (3D) encapsulation gels because of their ability to control cell phenotype through bio-specific cues. However, batch-to-batch variations, poor stability, cumbersome handling and relatively high costs strictly limit their use. Recently, a new substrate known as PhenoDrive-Y was used as 2D coating of tissue culture plastic showing to direct the bone marrow mesenchymal stromal cells (MSCs) towards the formation of 3D spheroids. When organised into 3D spheroids, the MSCs expressed levels of pluripotency markers and of paracrine angiogenic activity higher than MSCs adhering as fibroblast-like colonies on tissue culture plastic. The formation of the spheroids was attributed to the properties of this biomaterial that resembles the main features of the basement membrane by mimicking the mesh structure of Collagen IV and by presenting the cells with orderly spaced laminin bioligands. In this study, PhenoDrive-Y was compared to Matrigel for its ability to drive 2D co-cultures conditions of human endothelial cells and adult bone marrow MSCs into the formation of perivascular stem cell niche-like structures. Morphological analyses demonstrated that, when compared to Matrigel, PhenoDrive-Y led endothelial cells to sprout into a more consolidated tubular network and that MSCs nestled as compact spheroids above the anastomotic areas of this network to resemble more closely the histological features of the perivascular stem cell niche. A study of the expression of relevant markers led to the identification of the pathways linking the PhenoDrive-Y biomimetic properties to the acquired histological features demonstrating the enhanced levels of stemness, renewal potential, predisposition to migration, and paracrine activities of the MSCs.